Early life history of the pipe¢sh Nerophis lumbriciformis (Pisces: Syngnathidae) - Monteiro, Nuno Miguel (2012)
The embryonic and larval development of the pipe¢sh Nerophis lumbriciformis is described. The full development sequence lasted 30 d (at 14-15ºC), being shortened to 25-26 d at higher temperatures (16-17ºC), and hatching occurred throughout a 2^3 d period. Unlike species of the genus Syngnathus, the newly hatched larvae presented a functional mouth apparatus and the yolk sac completely absorbed.